2018
DOI: 10.1016/j.amepre.2017.09.008
|View full text |Cite|
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder by Gender and Veteran Status

Abstract: Post-traumatic stress disorder is a common mental health disorder that varies by gender and veteran status. Women veterans' high rates of post-traumatic stress disorder highlight a critical target for prevention and intervention, whereas understanding treatment barriers for men veterans and civilians is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
172
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 217 publications
(186 citation statements)
references
References 37 publications
12
172
1
1
Order By: Relevance
“…Nonetheless, two recent studies using nationally representative samples of the US population found higher prevalence of PTSD among women veterans, echoing gender differences in PTSD previously found in the general population [15, 16]. For example, a study using a nationally representative sample of the general population from the 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III) assessed differences in PTSD prevalence by both gender and veteran status [15], using Diagnostic and Statistical Manual of Mental Disorders—Fifth Edition (DSM-5) criteria [17]. Findings indicated that women veterans reported significantly higher prevalence of age-and race-adjusted lifetime and past-year PTSD (13.4%, 11.7%, respectively) than both women civilians (8.0%, 6.0%) and men veterans (7.7%, 6.7%) [15].…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Nonetheless, two recent studies using nationally representative samples of the US population found higher prevalence of PTSD among women veterans, echoing gender differences in PTSD previously found in the general population [15, 16]. For example, a study using a nationally representative sample of the general population from the 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III) assessed differences in PTSD prevalence by both gender and veteran status [15], using Diagnostic and Statistical Manual of Mental Disorders—Fifth Edition (DSM-5) criteria [17]. Findings indicated that women veterans reported significantly higher prevalence of age-and race-adjusted lifetime and past-year PTSD (13.4%, 11.7%, respectively) than both women civilians (8.0%, 6.0%) and men veterans (7.7%, 6.7%) [15].…”
Section: Introductionmentioning
confidence: 77%
“…Respondents further had to report symptom duration of ≥1 month and clinically significant impairment or distress. The requirement of ≥3 D and E symptoms is higher than the 2 symptoms from each cluster required for DSM-5 criteria [17], but has been used in other studies based on NESARC-III data [8, 15, 41]. Test–retest reliability of past-year PTSD was fair (0.41) and reliability of the dimensional PTSD criteria scale was good [intraclass correlation coefficient (ICC) = 0.69] [42].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations